Altered static and dynamic functional connectivity in major depressive disorder accompanied by high anxiety: evidence from the REST-meta-MDD consortium - Li, Lujun; Zeng, Zhijun; Zhou, Yaling; Lin, Jinfei; Li, Jiayuan (Frontiers in Psychiatry, 2025)
BackgroundMajor depressive disorder (MDD) is a prevalent mental health condition characterized by persistent low mood, diminished interest in pleasurable activities, and anhedonia. Some patients with depression experience high levels of anxiety, complicating clinical treatment. However, the underlying pathological mechanisms remain unclear.MethodsThe sample comprised 178 participants, including 73 MDD with high anxiety symptom subjects, 55 MDD with low anxiety symptom, and 50 healthy controls registered from multiple sites based on the REST-meta-MDD Project in China. Resting-state functional magnetic resonance imaging (rs-fMRI) data were recorded. Large-scale static and dynamic functional connectivity analyses were conducted to identify specific brain connectivity distinguishing MDD with low and high anxiety symptoms.ResultsWhile MDD patients with high and low anxiety symptoms exhibit overlapping alterations in dynamic functional connectivity between the auditory cortex and nodes of the salience network, their distinct clinical profiles may be associated with differential functional connectivity patterns between the components of the default mode network (DMN) and the visual network (VN), as well as between the components of the basal ganglia network (BGN) and VN.ConclusionThe VN–DMN–BGN functional circuit may help elucidate the underlying pathological mechanisms associated with varying levels of anxiety in depressive disorders. Understanding this neural correlation could contribute to the development of targeted therapeutic strategies for MDD.